2017
DOI: 10.1186/s11671-017-1875-5
|View full text |Cite
|
Sign up to set email alerts
|

TiO2-Based Nanomaterials for Gas Sensing—Influence of Anatase and Rutile Contributions

Abstract: The paper deals with application of three nanomaterial systems: undoped TiO2, chromium-doped TiO2:Cr and TiO2-SnO2 synthesized by flame spray synthesis (FSS) technique for hydrogen sensing. The emphasis is put on the role of anatase and rutile polymorphic forms of TiO2 in enhancing sensitivity towards reducing gases. Anatase-to-rutile transformation is achieved by annealing of undoped TiO2 in air at 700 °C, specific Cr doping and modification with SnO2. Undoped TiO2 and TiO2-SnO2 exhibit n-type behaviour and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…When the concentration is higher than 0.4 mol L À1 , the current density changes violently in the range of 0.85-1.30 A cm À2 . Earlier studies 7,8 have reported that the transformation temperature from anatase to rutile is in the range of 700-900 C. It means that when the supplied energy is high enough, anatase-TiO 2 can be transformed into rutile-TiO 2 . Combining the results of current density-time curves (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the concentration is higher than 0.4 mol L À1 , the current density changes violently in the range of 0.85-1.30 A cm À2 . Earlier studies 7,8 have reported that the transformation temperature from anatase to rutile is in the range of 700-900 C. It means that when the supplied energy is high enough, anatase-TiO 2 can be transformed into rutile-TiO 2 . Combining the results of current density-time curves (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Rutile is the stable phase, whereas anatase is metastable and tends to transform into rutile upon heating. 7,8 The rutile structure TiO 2 (rutile-TiO 2 ) has even more applications, such as a photocatalytic material, white pigment, in cosmetics and as an electrode material for lithium-ion batteries. [9][10][11] In addition, the mixed phase structures have been researched for some new properties and synergetic effects due to the interface lattice mismatch between the two phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, an electron transfer mechanism is suggested (Figure ). The band gap of rutile and anatase TiO 2 is 3.0 eV and 3.2 eV, respectively ,. While, the energy of conduction band (bottom) of rutile is higher than that of anatase.…”
Section: Resultsmentioning
confidence: 91%
“…The peak maximum of TiO 2 NSs films occurs at approximately 370 nm and the films have no significant absorption for visible light due to the large band gap of TiO 2 [22,23]. However, after coating with MAPbI 3 , the TiO 2 NSs/MAPbI 3 films present excellent absorption capacity from 350 to 800 nm, and the absorption intensity increased substantially.…”
Section: Resultsmentioning
confidence: 99%